Ultra-thin erosion-resistant blade and preparation method thereof
Through the combination of multi-channel variable speed ultra-high-speed laser cladding technology and NiCr transition layer, the low coating quality and blade deformation caused by heat storage in traditional technology were solved, and a nickel-based Cr3C2 with high microhardness and good bonding to the matrix was prepared. -NiCr gradient erosion-resistant coating significantly improves corrosion resistance.
Patent Information
- Application Number
- CN202310366892.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-04-07
AI Technical Summary
Traditional ultra-high-speed laser cladding technology has problems such as heat storage leading to low coating quality and blade deformation when preparing erosion-resistant blades. Moreover, the physical properties of nickel-based coatings vary greatly from the matrix, making it difficult to obtain good cladding effect. .
Using multi-channel variable speed ultra-high-speed laser cladding technology, the NiCr transition layer is cold sprayed on the surface of the stainless steel blade substrate and performs multi-channel variable speed laser cladding on it to control the melt pool temperature and scanning speed, and the microhardness is prepared with high microhardness and high-quality microhardness and A well-bound nickel-based Cr3C2-NiCr gradient erosion-resistant coating with a matrix.
It significantly improves the continuity, uniformity and hardness of the coating, reduces the deformation and erosion wear of the blade, the microhardness is no less than 1800HV0.2, and the erosion wear is small, which significantly improves the erosion resistance.
Smart Images

Figure CN116497348B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparing surface coatings by ultra-high-speed laser cladding, and in particular to an ultra-thin erosion-resistant blade and a preparation method thereof. Background Art
[0002] As a general mechanical equipment, pumps are widely used in various fields of the national economy. The blades and impellers of the pumps are mostly made of carbon steel, stainless steel and other materials. During use, the material particles and sand particles continuously impact and scour the pump, which easily leads to serious wear of the blades and impellers. Therefore, it is necessary to use surface modification technology to prepare coatings with improved surface properties to increase the service life of mechanical parts. Although there are many technologies (electrodeposition, physical vapor deposition, chemical vapor deposition, etc.) that can be used for coating preparation, each process has its limitations. For example, the bonding strength of coatings developed by physical or chemical vapor deposition technology is low, and the repeatability and controllability of electrodeposition are poor. The coating prepared by ultra-high-speed laser cladding technology has the advantages of high hardness, high bonding strength due to metallurgical bonding with the substrate, low dilution rate to the substrate and low thermal impact. It is used to solve the erosion and wear problems of service parts in harsh environments and can better break through the above limitations.
[0003] At present, the use of traditional ultra-high-speed laser cladding technology to prepare erosion-resistant blade coatings has the following problems:
[0004] 1. Traditional ultra-high-speed laser cladding technology has defects. Traditional ultra-high-speed multi-pass laser cladding works at a uniform speed. The heat storage during the processing can not only reheat the previous track coating, but also preheat the subsequent track coating substrate. However, as the number of tracks increases, the substrate temperature of the subsequent track coating will become higher and higher, which will cause the thinner blades (thickness 2 to 4 mm) to deform violently, affecting the service life of the prepared blades and the application scope of the technology (the applicable blade thickness cannot be too thin, otherwise it is easy to deform due to heat).
[0005] 2. In the erosion and wear resistant cladding material system, the performance of nickel-based coatings has great defects. Although adding hard ceramic particles (WC, Cr3C2, etc.) or suitable elements to nickel powder can improve the performance of nickel-based composite coatings, there are also problems such as large differences in physical properties between the substrate and the coating material, making it difficult to obtain a good cladding effect.
[0006] Zang Chuncheng et al. used the traditional non-speed laser cladding technology with a maximum laser power of 3KW to clad the NiCr-Cr3C2 coating on the steel surface. The microhardness of the cladding layer can reach up to 1660HV. 0.2, about 6 times that of the substrate, so that the cladding layer has good wear resistance. (Zang Chuncheng, Wang Yanzhong, Zhang Yidu. Microstructure and hardness characteristics of laser cladding specific material coatings [J]. Laser & Infrared, 2015, 45(08): 897-901.). However, if the traditional non-variable speed laser cladding technology is directly transplanted to the preparation of erosion-resistant coatings on the surface of pump blades, the heat input of the traditional non-variable speed laser cladding technology has a greater impact on the thinner substrate (thickness 2 to 4 mm) of the pump blades, and the blades are easily deformed and difficult to apply. The present invention adopts multi-channel variable speed ultra-high-speed laser cladding technology. The scanning speed increases continuously within a certain range, and the heat input is small. It can prepare microhardness (not less than 1800HV) on a thinner blade substrate. 0.2 ) and a nickel-based Cr3C2-NiCr gradient anti-erosion coating with no deformation of the substrate.
[0007] Lin Chenghu et al. used a laser cladding technology with an input power of 3KW to prepare an in-situ self-generated nickel-based chromium carbide composite coating on the steel surface. The microhardness of the cladding layer can reach up to 930HV, and the average hardness is about 3.5 times that of the substrate, making the cladding layer have good wear resistance. (Lin Chenghu, Ren Jingri, He Chunlin. Microstructure characteristics of laser in-situ chromium carbide-nickel-based composite coating [J]. Laser Technology, 2014, 38(02): 186-190.) However, if it is directly transplanted to the surface of the pump blade to prepare the erosion-resistant coating, it is difficult to obtain a good cladding effect due to the large difference in physical properties between the substrate and the coating material. In addition, as the chromium carbide hard phase is generated, the thermal conductivity decreases, resulting in the generation of thermal stress, which makes the coating prone to cracks. The present invention adopts 3000-3500W multi-channel variable speed ultra-high-speed laser cladding technology, uses NiCr as a transition layer, and has a good combination with the substrate and the laser cladding layer. As the scanning speed increases within a certain range, the heat input decreases, and it is possible to prepare a microhardness of not less than 1800HV 0.2 ), a nickel-based Cr3C2-NiCr gradient anti-erosion coating with good bonding with the substrate, no cracks, and small erosion wear (4.1-4.4 mg). Summary of the invention
[0008] The present invention provides a method for preparing ultra-thin erosion-resistant blades, which can effectively solve the problems of low coating quality and blade deformation caused by heat accumulation in the existing multi-pass ultra-high-speed laser cladding process. According to scanning electron microscopy and X-ray diffraction (XRD) analysis, the erosion-resistant coating prepared by the variable-speed ultra-high-speed laser cladding of the present invention is continuous, complete, uniform and dense, and the coating microstructure is fine and uniform grains of 0.1 to 2 μm. The cladding layer contains a Cr3C2 reinforcement phase that is well bonded to the substrate and has a very high hardness, which significantly improves the substrate hardness and wear resistance, and the microhardness is not less than 1800 HV 0.2 , and there is almost no deformation problem such as warping of the substrate.
[0009] The specific technical solutions are as follows:
[0010] A method for preparing an ultra-thin erosion-resistant blade, the ultra-thin erosion-resistant blade comprising a stainless steel blade substrate with a thickness of 2 to 4 mm, a NiCr transition layer with a buffering and energy-absorbing function prepared on the surface of the stainless steel blade substrate by cold spraying, and a nickel-based chromium carbide erosion-resistant coating prepared on the NiCr transition layer by a multi-pass variable speed ultra-high-speed laser cladding technology;
[0011] The preparation method comprises the steps of:
[0012] 1) A NiCr transition layer with a buffering and energy-absorbing function having a porosity of 5% to 8% and a thickness of 100 to 200 μm is prepared on the surface of a stainless steel blade substrate by cold spraying;
[0013] 2) A nickel-based chromium carbide erosion-resistant coating is prepared on the NiCr transition layer using a multi-pass variable speed ultra-high-speed laser cladding technology: During the multi-pass ultra-high-speed laser cladding process, a uniform speed scan is first performed, and when the molten pool temperature reaches 10% to 25% of the melting point of the nickel-based chromium carbide erosion-resistant coating material in degrees Celsius, the scanning speed is gradually increased until the cladding is completed, and the scanning speed is always maintained in the range of 10 to 100 mm / s during the entire laser cladding process, and the molten pool temperature never exceeds 130% of the melting point of the stainless steel blade substrate material in degrees Celsius.
[0014] In the method for preparing the erosion-resistant blade of the present invention, at least the following points need to be taken into consideration:
[0015] 1. When the molten pool temperature reaches 10% to 25% of the melting point of the nickel-based chromium carbide erosion-resistant coating material in degrees Celsius, it means that the heat storage of the blade has begun to accumulate. At this time, the scanning speed needs to be increased and the cladding time needs to be shortened to avoid overheating and deformation of the blade.
[0016] 2. During the entire laser cladding process, the molten pool temperature never exceeds 130% of the melting point of the stainless steel blade matrix material in degrees Celsius. This is also a necessary requirement to avoid overheating and deformation of the blade. Under such a requirement, it means that the scanning speed cannot be too slow.
[0017] 3. The scanning speed should not be too fast. Commercially available Ni60 and Cr3C2 powder raw materials and the blades themselves usually contain impurity elements such as Cr and B. Too fast a scanning speed will lead to insufficient melting of refractory impurity elements, which will lead to a decrease in coating quality and reduced erosion resistance.
[0018] 4. The nickel-based chromium carbide erosion-resistant coating has poor effect when in direct contact with the stainless steel blade substrate. The present invention introduces an intermediate transition layer of NiCr.
[0019] In the method for preparing the erosion-resistant blade of the present invention, a temperature sensing device can be used to detect the temperature of the molten pool in real time.
[0020] The method for preparing the erosion-resistant blade of the present invention is particularly suitable for the case where the blade base material is stainless steel.
[0021] In a preferred embodiment, in step 1), before cold spraying the NiCr transition layer on the surface of the stainless steel blade substrate, the surface of the stainless steel blade substrate is pre-treated by grinding and polishing to make the roughness Ra of the surface of the stainless steel blade substrate less than 6.4 μm.
[0022] After the pretreatment of grinding and polishing, the blades can be cleaned with deionized water, dried at high temperature, and then placed on the workbench waiting for subsequent operations.
[0023] In a preferred example, in step 1), the specific parameter conditions of the cold spraying are: the spraying gas is nitrogen, the spraying temperature is 400-500°C, the spraying pressure is 2-3MPa, the spraying distance is 20-25mm, the powder feeding speed is 50-60g / min, and the spray gun moving speed is 80-100mm / s.
[0024] In a preferred example, in step 1), the method for preparing the spraying material used for cold spraying the NiCr transition layer includes: mixing Ni powder and Cr powder with a particle size of 35 to 80 μm in a mass ratio of 20 to 30:70 to 80 and ball milling to obtain the spraying material.
[0025] In a preferred example, in step 2), the multi-pass variable speed ultra-high-speed laser cladding technology is also designed with the following parameter conditions: the laser beam is focused at 0 to 9 mm above the cladding surface, the laser power is 3000 to 3500 W, argon is used as the protective gas, the powder feeding rate is 0.6 to 3.0 L / min, and the scanning speed is increased at a rate of 1 to 10 mm / s per second during the speed change process until the cladding is completed.
[0026] In step 2):
[0027] For small and medium-sized impeller blades with an outer diameter of 30-300 mm, preferably, when the molten pool temperature reaches 10% to 15% of the melting point of the nickel-based chromium carbide erosion-resistant coating material in degrees Celsius, the scanning speed is gradually increased at a rate of 6 to 10 mm / s per second until the cladding is completed;
[0028] For large impeller blades with an outer diameter greater than 300 mm, preferably, when the molten pool temperature is 15% but not more than 25% higher than the melting point of the nickel-based chromium carbide erosion-resistant coating material in degrees Celsius, the scanning speed is gradually increased at a rate of 1 to 6 mm / s per second until the cladding is completed.
[0029] In a preferred example, in step 2), the method for preparing the cladding material used for preparing the nickel-based chromium carbide erosion-resistant coating by multi-pass variable speed ultra-high-speed laser cladding technology includes: mixing Ni60 powder and Cr3C2 powder with particle sizes of 50-70μm and 45-55μm respectively in a mass ratio of 20-30:70-80 and ball milling to obtain the cladding material.
[0030] According to the method for preparing the erosion-resistant blade of the present invention, after the cladding is completed, the surface coating of the blade after the cladding treatment can be ground as needed, and the roughness range can be 0.4 to 1.6 μm.
[0031] As a general inventive concept, the present invention also provides an ultra-thin erosion-resistant blade prepared by the preparation method. The erosion-resistant coating is continuous, complete, uniform and dense, the coating microstructure is fine and uniform grains of 0.1 to 2 μm, and the microhardness is not less than 1800 HV 0.2 .
[0032] In a preferred example, the total thickness of the NiCr transition layer and the erosion-resistant coating is 300-1000 μm.
[0033] Preferably, in the nickel-based chromium carbide erosion-resistant coating, the mass proportion of NiCr is 25% to 30%, and the mass proportion of Cr3C2 is 50% to 65%.
[0034] The erosion-resistant coating prepared by the present invention has no cracks and obvious pores. In the erosion wear experiment, it is found that when the impact angle is 30° to 90°, the coating wear weight loss is reduced by 26% to 35% compared with the loss of the nickel-based Cr3C2-NiCr gradient erosion-resistant coating prepared by the traditional uniform speed ultra-high-speed laser cladding technology, indicating that the erosion resistance of the coating is significantly improved.
[0035] Compared with the prior art, the present invention has the following main advantages:
[0036] The present invention uses cold spraying to prepare a NiCr transition layer on the blade surface. The NiCr transition layer has a certain amount of pores and is well bonded to the stainless steel blade substrate and the laser cladding layer, so it can buffer and absorb the energy generated by heat storage. Multiple variable-speed ultra-high-speed laser cladding is used to clad the Ni-based Cr3C2 powder on the blade surface to prepare an erosion-resistant coating. This can effectively reduce the large thermal stress caused by heat storage during the coating preparation process using multiple ultra-high-speed laser cladding, which reduces the coating quality and causes blade deformation. The total thickness of the prepared nickel-based Cr3C2-NiCr gradient erosion-resistant coating and NiCr transition layer can be designed to be 300 to 1000 μm, and the microhardness can reach 1800 HV 0.2There are no cracks or obvious pores. In the erosion wear experiment, it was found that when the impact angle was 30°~90°, the coating wear loss was 4.1~4.4 mg, which was 26%~35% less than that of the nickel-based Cr3C2-NiCr gradient erosion-resistant coating prepared by traditional uniform-speed ultra-high-speed laser cladding technology. This shows that the erosion resistance of the coating is significantly improved, which provides a reference for the in-depth study of nickel-based composite coatings and their promotion and application under erosion wear conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic front view of the variable speed ultra-high speed laser cladding process of the present invention;
[0038] Figure 2 A schematic diagram of a stainless steel blade substrate and an erosion-resistant blade coating on its surface according to the present invention;
[0039] In the figure:
[0040] 1-Stainless steel blade substrate with NiCr transition layer on the surface;
[0041] 2-Automatic speed-changing ultra-high-speed laser cladding equipment with sensors and controllers;
[0042] 3-Nickel-based Cr3C2-NiCr erosion-resistant coating;
[0043] 4-Stainless steel blade base;
[0044] 5-NiCr transition layer;
[0045] 6-Nickel-based chromium carbide erosion-resistant coating. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0047] like Figure 1 As shown, the variable speed ultra-high speed laser cladding of the present invention uses an automatic variable speed ultra-high speed laser cladding device 2 with a sensor device and a controller to perform multiple laser cladding on the surface of a stainless steel blade substrate 1 with a NiCr transition layer on the surface to prepare a nickel-based Cr3C2-NiCr erosion-resistant coating 3.
[0048] The stainless steel blade substrate and the erosion-resistant blade coating on its surface are as follows: Figure 2 As shown, the middle is a NiCr transition layer with a porosity of 5% to 8% and a thickness of 100 to 200 μm cold-sprayed on a stainless steel blade substrate and has a buffering and energy-absorbing effect, and the top is a nickel-based Cr3C2 cladding layer.
[0049] Comparative Example 1
[0050] 1. First, grind and polish the surface of the 3mm thick small and medium-sized stainless steel pump blade substrate to make the blade surface roughness Ra 3.2μm, and clean it with deionized water, and place it on the workbench after cleaning and drying.
[0051] 2. The mixed powder of Ni60 (particle size 50-70 μm) and Cr3C2 (particle size 45-55 μm) with a mass ratio of 25:75 is fully ball-milled to obtain the cladding material, and Ni (particle size 35-80 μm) and Cr (particle size 35-80 μm) with a mass ratio of 25:75 is fully ball-milled to obtain the NiCr transition layer material.
[0052] 3. Use high-pressure cold spraying equipment, with nitrogen as the spraying gas, spraying temperature at 500°C, spraying pressure at 2MPa, spraying distance at 25mm, powder feeding speed at 60g / min, and spray gun moving speed at 100mm / s to prepare a NiCr transition layer with a coating thickness of about 200μm and a porosity of about 8% on the blade surface.
[0053] Fourth, the laser beam was focused at 6mm above the cladding surface, the laser power was 3000W, argon was used as the protective gas, and the powder feeding rate was 1.5L / min and the scanning speed was 15mm / s. The cladding surface was scanned at a uniform speed until the cladding was completed. Finally, a nickel-based Cr3C2-NiCr gradient coating with a thickness of about 693μm and an overlap rate of 50% was obtained. The microhardness of the coating is 1610HV 0.2 There are no obvious cracks but there is a porosity of about 3.8%. The NiCr content accounts for 20.6wt%, the Cr3C2 content accounts for 47.2wt%, and the blade base (3mm thick) has a 1.5° warping deformation.
[0054] 5. The surface coating of the blade after cladding treatment is ground to a roughness of 0.6 μm to finally obtain the finished product.
[0055] 6. The erosion test at an impact angle of 60° showed that the coating wear weight loss was approximately 6.2 mg.
[0056] Comparative Example 2
[0057] 1. First, grind and polish the surface of the large stainless steel pump blade substrate with a thickness of 3mm to make the blade surface roughness Ra 3.2μm, and clean it with deionized water, and place it on the workbench after cleaning and drying.
[0058] 2. The mixed powder of Ni60 (particle size 50-70 μm) and Cr3C2 (particle size 45-55 μm) with a mass ratio of 25:75 is fully ball-milled to obtain the cladding material.
[0059] 3. Turn on the ultra-high-speed laser cladding head, focus the laser beam on the cladding surface, and preheat the surface of the substrate.
[0060] Fourth, focus the laser beam 6mm above the cladding surface, with a laser power of 3000W and argon as the protective gas. Scan the first few cladding surface positions in sequence at a uniform speed with a powder feeding rate of 1.5L / min and a scanning speed of 15mm / s. When the molten pool temperature reaches 20% of the melting point (degrees Celsius) of the coating material, the scanning speed is increased at a rate of 5mm / s per second until the cladding is completed (finally 60mm / s). When the cladding is completed, the molten pool temperature reaches about 124% of the melting point (degrees Celsius) of the base material. Finally, a nickel-based Cr3C2 composite coating with a thickness of about 352μm and an overlap rate of 50% is obtained. The microhardness of the coating is 1710HV 0.2 The coating has a small amount of cracks and a porosity of about 2.6%, and the blade substrate (3mm thick) has a 0.7° warping deformation.
[0061] 5. The surface coating of the blade after cladding treatment is ground to a roughness of 0.6 μm to finally obtain the finished product.
[0062] 6. The erosion test at an impact angle of 60° showed that the coating wear weight loss was approximately 5.88 mg.
[0063] Example 1
[0064] 1. First, grind and polish the surface of the 3mm thick small and medium-sized stainless steel pump blade substrate to make the blade surface roughness Ra 3.2μm, and clean it with deionized water, and place it on the workbench after cleaning and drying.
[0065] 2. The mixed powder of Ni60 (particle size 50-70 μm) and Cr3C2 (particle size 45-55 μm) with a mass ratio of 25:75 is fully ball-milled to obtain the cladding material, and Ni (particle size 35-80 μm) and Cr (particle size 35-80 μm) with a mass ratio of 25:75 are fully ball-milled to obtain the NiCr transition layer material.
[0066] 3. Use high-pressure cold spraying equipment, with nitrogen as the spraying gas, spraying temperature at 500°C, spraying pressure at 2MPa, spraying distance at 25mm, powder feeding speed at 60g / min, and spray gun moving speed at 100mm / s to prepare a NiCr transition layer with a coating thickness of about 200μm and a porosity of about 8% on the blade surface.
[0067] Fourth, focus the laser beam 6mm above the cladding surface, with a laser power of 3000W and argon as the protective gas. Scan the first few cladding surfaces in sequence at a uniform speed with a powder feeding rate of 1.5L / min and a scanning speed of 15mm / s. When the molten pool temperature reaches 12% of the melting point (degrees Celsius) of the nickel-based chromium carbide erosion-resistant coating material, increase the scanning speed at a rate of 7mm / s per second until the cladding is completed (finally 50mm / s). When the cladding is completed, the molten pool temperature reaches about 120% of the melting point (degrees Celsius) of the base material. A nickel-based Cr3C2-NiCr gradient coating with a thickness of about 518μm and an overlap rate of 50% is obtained. The coating is continuous, complete, uniform and dense, and the coating microstructure is small and uniform grains of 0.1 to 2μm. The microhardness of the coating is 1830HV 0.2 , no cracks and obvious pores, the NiCr content accounts for 29.2wt%, the Cr3C2 content accounts for 63.5wt%, and the blade matrix has no warping deformation.
[0068] 5. The surface coating of the blade after cladding treatment is ground to a roughness of 0.6 μm to finally obtain the finished product.
[0069] 6. The erosion test at an impact angle of 60° measured a coating wear loss of approximately 4.1 mg, which was reduced by (6.2-4.1) / 6.2=33.9% compared with the nickel-based Cr3C2-NiCr gradient coating prepared by conventional uniform-speed ultra-high-speed laser cladding technology (Comparative Example 1).
[0070] Example 2
[0071] 1. First, grind and polish the surface of the large stainless steel pump blade substrate with a thickness of 3mm to make the blade surface roughness Ra 3.2μm, and clean it with deionized water, and place it on the workbench after cleaning and drying.
[0072] 2. The mixed powder of Ni60 (particle size 50-70 μm) and Cr3C2 (particle size 45-55 μm) with a mass ratio of 25:75 is fully ball-milled to obtain the cladding material, and Ni (particle size 35-80 μm) and Cr (particle size 35-80 μm) with a mass ratio of 25:75 are fully ball-milled to obtain the NiCr transition layer material.
[0073] 3. Use high-pressure cold spraying equipment, with nitrogen as the spraying gas, spraying temperature at 500°C, spraying pressure at 2MPa, spraying distance at 25mm, powder feeding speed at 60g / min, and spray gun moving speed at 100mm / s to prepare a NiCr transition layer with a coating thickness of about 200μm and a porosity of about 8% on the blade surface.
[0074] Fourth, focus the laser beam 6mm above the cladding surface, with a laser power of 3000W and argon as the protective gas. Scan the first few cladding surface positions in sequence at a uniform speed with a powder feeding rate of 1.5L / min and a scanning speed of 15mm / s. When the molten pool temperature reaches 20% of the melting point (degrees Celsius) of the nickel-based chromium carbide erosion-resistant coating material, the scanning speed is increased at a rate of 5mm / s per second until the cladding is completed (finally 50mm / s). When the cladding is completed, the molten pool temperature reaches about 115% of the melting point (degrees Celsius) of the base material. A nickel-based Cr3C2-NiCr gradient coating with a thickness of about 573μm and an overlap rate of 50% is obtained. The coating is continuous, complete, uniform and dense, and the coating microstructure is fine and uniform grains of 0.1 to 2μm. The microhardness of the coating is 1810HV 0.2 , no cracks and obvious pores, the NiCr content accounts for 28.6wt%, the Cr3C2 content accounts for 59.2wt%, and the blade matrix has no warping deformation.
[0075] 5. The surface coating of the blade after cladding treatment is ground to a roughness of 0.6 μm to finally obtain the finished product.
[0076] 6. The erosion test at an impact angle of 60° measured a coating wear loss of approximately 4.32 mg, which was reduced by (5.88-4.32) / 5.88=26.5% compared with the nickel-based Cr3C2 composite coating without a NiCr transition layer prepared by variable speed ultra-high-speed laser cladding technology (Comparative Example 2).
[0077] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing an ultra-thin erosion-resistant blade, characterized in that: The ultra-thin erosion-resistant blade comprises a stainless steel blade substrate with a thickness of 2 to 4 mm, a NiCr transition layer with a buffering and energy-absorbing function prepared on the surface of the stainless steel blade substrate by cold spraying, and a nickel-based chromium carbide erosion-resistant coating prepared on the NiCr transition layer by using a multi-pass variable speed ultra-high-speed laser cladding technology; The preparation method comprises the steps of: 1) A NiCr transition layer with a buffering and energy-absorbing function having a porosity of 5% to 8% and a thickness of 100 to 200 μm is prepared on the surface of a stainless steel blade substrate by cold spraying; 2) A nickel-based chromium carbide erosion-resistant coating is prepared on the NiCr transition layer using a multi-pass variable speed ultra-high-speed laser cladding technology: During the multi-pass ultra-high-speed laser cladding process, a uniform speed scan is first performed, and when the molten pool temperature reaches 10% to 25% of the melting point of the nickel-based chromium carbide erosion-resistant coating material in degrees Celsius, the scanning speed is gradually increased until the cladding is completed, and the scanning speed is always maintained in the range of 10 to 100 mm / s during the entire laser cladding process, and the molten pool temperature never exceeds 130% of the melting point of the stainless steel blade substrate material in degrees Celsius.
2. The preparation method according to claim 1, characterized in that: In step 1), before cold spraying the NiCr transition layer on the surface of the stainless steel blade substrate, the surface of the stainless steel blade substrate is pre-treated by grinding and polishing to make the roughness Ra of the surface of the stainless steel blade substrate less than 6.4 μm.
3. The preparation method according to claim 1, characterized in that: In step 1), the specific parameter conditions of the cold spraying are: the spraying gas is nitrogen, the spraying temperature is 400-500°C, the spraying pressure is 2-3MPa, the spraying distance is 20-25mm, the powder feeding speed is 50-60g / min, and the spray gun moving speed is 80-100mm / s.
4. The preparation method according to claim 1, characterized in that: In step 1), the method for preparing the spraying material used for cold spraying the NiCr transition layer comprises: mixing Ni powder and Cr powder with a particle size of 35 to 80 μm in a mass ratio of 20 to 30:70 to 80 and ball milling to obtain the spraying material.
5. The preparation method according to claim 1, characterized in that: In step 2), the multi-pass variable speed ultra-high-speed laser cladding technology also designs the following parameter conditions: the laser beam is focused at 0 to 9 mm above the cladding surface, the laser power is 3000 to 3500 W, argon is used as the protective gas, the powder feeding rate is 0.6 to 3.0 L / min, and the scanning speed is increased at a rate of 1 to 10 mm / s per second during the speed change process until the cladding is completed.
6. The preparation method according to claim 1, characterized in that: In step 2): For small and medium-sized impeller blades with an outer diameter of 30-300 mm, when the molten pool temperature reaches 10% to 15% of the melting point of the nickel-based chromium carbide erosion-resistant coating material in degrees Celsius, the scanning speed is gradually increased at a rate of 6 to 10 mm / s per second until the cladding is completed; For large impeller blades with an outer diameter greater than 300 mm, when the molten pool temperature is 15% but not more than 25% higher than the melting point of the nickel-based chromium carbide erosion-resistant coating material in degrees Celsius, the scanning speed is gradually increased at a rate of 1 to 6 mm / s per second until the cladding is completed.
7. The preparation method according to claim 1, characterized in that: In step 2), the method for preparing the cladding material used for preparing the nickel-based chromium carbide erosion-resistant coating by multi-pass variable speed ultra-high-speed laser cladding technology includes: mixing Ni60 powder and Cr3C2 powder with particle sizes of 50-70μm and 45-55μm respectively in a mass ratio of 20-30:70-80 and ball milling to obtain the cladding material.
8. The ultra-thin erosion-resistant blade prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The erosion-resistant coating is continuous, complete, uniform and dense, the coating microstructure is fine and uniform grains of 0.1 to 2 μm, and the microhardness is not less than 1800 HV 0.2 .
9. The ultra-thin erosion-resistant blade according to claim 8, characterized in that: The total thickness of the NiCr transition layer and the erosion-resistant coating is 300-1000 μm.
10. The ultra-thin erosion-resistant blade according to claim 8, characterized in that: In the nickel-based chromium carbide erosion-resistant coating, the mass proportion of NiCr is 25% to 30%, and the mass proportion of Cr3C2 is 50% to 65%.
Citation Information
Patent Citations
Anti-scuffing treatment method for surface of water turbine
CN103510035A
Boron cast iron air cylinder sleeve carbon scraping ring coating and preparation and spraying method thereof
CN106978581A